Reformation and Birth of Modern Democracy: Lessons for Contemporary Nigerian Christians - Nwaozuru Johnmajor Chinecherem; Nwokedi Godswill Okechukwu (Darul Yasin Al Sys, 2026)
Christianity originated in Jewish territory and was initially regarded as an illegal religion when it expanded across the Roman Empire; however, its legalization under Emperor Constantine facilitated its increasing involvement in political affairs. Although the sixteenth-century Reformation led by Martin Luther was primarily religious in orientation, its adoption by King Henry VIII of England transformed it into a broader religio-political movement. John Calvin further extended the Reformation’s political significance by criticizing practices within the Roman Catholic Church and emphasizing principles of good governance, particularly through Institutes of the Christian Religion, which articulated ideas concerning just civil government that contributed to the development of modern democratic thought. This study examines the influence of religion on politics by analyzing the Reformation movement in Western Europe and its subsequent role in shaping modern democracy. It also addresses the limited political participation of some eligible Christian citizens in Nigeria, a condition that may contribute to the persistence of poor governance. The study employed a qualitative library research design based on secondary sources, including books, journal articles, magazines, newspapers, edited volumes, and relevant online documents. The analysis indicates that the Reformation evolved beyond a religious movement and became an important political force that influenced ideas of governance, civic responsibility, and democracy. The study concludes that Christian political participation, when guided by Christian ethical principles, can contribute to improved governance and democratic development in Nigeria. It therefore recommends greater and more responsible involvement of Nigerian Christians in political processes to support the societal change they seek.